2016
DOI: 10.28978/nesciences.286032
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of the Red Sea goatfish Parupeneus forsskali (Fourmanoir & Guézé, 1976) (Perciformes: Mullidae) from Iskenderun Bay, Northeastern Mediterranean

Abstract: On 15 March 2015, a single specimen of Parupeneus forsskali (Fourmanoir & Guézé, 1976) was captured by a trammel net at a depth of 30 m from Iskenderun Bay. The occurrence of the Red Sea goatfish P. forsskali was reported for the first time in the Iskenderun Bay and the first captured data for the Turkish marine waters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Sonin et al (2013) have reported the species during the same period from the coast of Israel. The species has also been reported by Iglesias & Frotte (2015) off the coast of Cyprus and Gürlek et al (2016) off the coast of Iskenderun (Turkey). P. forsskåli is reported from the Gulf of Antalya for the first time.…”
Section: A Steriotimentioning
confidence: 80%
“…Sonin et al (2013) have reported the species during the same period from the coast of Israel. The species has also been reported by Iglesias & Frotte (2015) off the coast of Cyprus and Gürlek et al (2016) off the coast of Iskenderun (Turkey). P. forsskåli is reported from the Gulf of Antalya for the first time.…”
Section: A Steriotimentioning
confidence: 80%
“…The number of lessepsian species has increased dramatically during the last decade in Turkish marine waters (Turan et al, 2015;Gürlek et al, 2016;Gurlek et al, 2016a,b). Especially, physical conditions in the eastern Mediterranean are changing over the last decades (Turan et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…After this date, P. forsskali was reported from several locations by Sonin et al (2013) from southern edge of Haifa Bay, Israel; by Iglésias and Frotté (2015) from Agia Triada, Cyprus; By Gurlek et al (2016) from İskenderun Bay, by Yağlıoğlu and Ayas (2016) from Yeşilovacık, Turkey; by Mehanna et al (2016) from Alexandria, Egypt; by Ali et al, 2016 from Jableh, Syria (Figure 2). In the current study, it is reported from North of Cyprus and gulf of Antalya (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…In the current study, it is reported from North of Cyprus and gulf of Antalya (Table 1). Çınar et al, 2006 Mersin, Turkey ---------------------- Bariche et al, 2013 Beirut, Lebanon 33°55'N; 35°34'E Sonin et al, 2013 Haifa Bay, Israel 32°51′N;34°56′E Iglésias and Frotté, 2015 Agia Triada, Cyprus 35° 3′ N; 34°01'E Gurlek et al, 2016 İskenderun Bay, Turkey 36°21'N; 35°49 'E Mehanna et al,, 2016 Alexandria, Egypt 31°16'N; 30°10'E Ali et al, 2016 Jableh According to all of these reports from different locations of Mediterranean Sea, the population of P. forsskali may be established in the eastern Mediterranean Sea. Also, according to latest reports on the south of Turkey, it is expanding westward along to Turkey Mediterranean coasts.…”
Section: Resultsmentioning
confidence: 99%